Electrical and magnetic properties of silicon carbide composites with titanium and niobium carbide as sintering aids. Issue 3 (1st February 2023) - Bystrický, R.; Škrátek, M.; Rusnák, J.; Precner, M.; Ťapajna, M.; Hnatko, M.; Šajgalík, P.
Abstract: Silicon carbide based composites with 30, 40 and 50 wt % of Ti and NbC as sintering additives were prepared by hot-press method. Molar ratio of Ti:NbC was kept at 1:1.8. The two step sintering was performed in order to avoid the squeezing out the melted titanium above 1668 °C. Composite powders were sintered at 1650 °C for 3 h and subsequently at 1850 °C for 1 h under mechanical pressure of 30 MPa in Ar atmosphere. XRD pattern confirmed the formation of (Ti, Nb)Css in the SiC matrix. Composite with 50% of Ti–NbC phase showed the extraordinary electrical conductivity of 2.4 × 10 5  S/m which was achieved by homogeneous distribution of Ti and NbC in SiC matrix and forming a continuous conductive network. Prepared composites show complex magnetic properties, diamagnetism originated from SiC matrix, paramagnetism caused by Ti and NbC admixing, as well as weak ferromagnetism probably coming from impurities contained in the initial powders. Samples with 30 and 40 wt % of Ti and NbC exhibit superconducting state below 2 K.